Transformasi Pembelajaran Pendidikan Agama Islam melalui Artificial Intelligence di Era Society 5.0 - Sucipto Sucipto; Hardika Saputra (Al-Jinan : Jurnal Studi Islam, 2026)
The development of Artificial Intelligence in the Society 5.0 era encourages the transformation of Islamic Religious Education learning to become more innovative and adaptive. However, studies on the effectiveness of Artificial Intelligence in Islamic Religious Education remain limited. This study aims to analyze the transformation of Islamic Religious Education learning through Artificial Intelligence in the Society 5.0 era. The research employed a Systematic Literature Review method with a descriptive qualitative approach. Data were collected from national and international scientific articles published between 2020 and 2026 through Google Scholar, Scopus, DOAJ, and Garuda. The results indicate that Artificial Intelligence improves learning motivation, learning effectiveness, personalized learning, and interactive learning media development. Artificial Intelligence also supports Islamic digital literacy and learning flexibility. However, its implementation still faces challenges such as low digital literacy among educators, limited infrastructure, and ethical issues in technology use. This study concludes that Artificial Intelligence has significant potential to support the transformation of Islamic Religious Education learning in the Society 5.0 era.